The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.15376/biores.9.4.6117-6129
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carboxymethyl Cellulose Addition on the Properties of Starch-based Wood Adhesive

Abstract: Starch adhesive was prepared utilizing corn starch, polyvinyl alcohol, and borax as raw materials. A certain amount of water-soluble carboxymethyl cellulose (CMC) was added in the preparation process, and a certain percentage of polymethylene polyphenylene isocyanate pre-polymer as cross-linking agent was used to improve its water resistance. To evaluate the water resistance, three-layer plywood was fabricated by hot pressing, and bonding strength was measured using a mechanical testing machine according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…However, the t-test indicated no significant differences between samples of the starch adhesives because of the high variance of results, likely due to more challenging curing of starch in the presence of high moisture content and absence of heat treatment. The trend is in fair agreement with Qiao et al (2014), who found similar behaviour in CMC addition to starch in plywood and the optimal benefit from only 0.375% CMC dose, while higher concentrations produced weaker bond strength.…”
Section: Resultssupporting
confidence: 89%
“…However, the t-test indicated no significant differences between samples of the starch adhesives because of the high variance of results, likely due to more challenging curing of starch in the presence of high moisture content and absence of heat treatment. The trend is in fair agreement with Qiao et al (2014), who found similar behaviour in CMC addition to starch in plywood and the optimal benefit from only 0.375% CMC dose, while higher concentrations produced weaker bond strength.…”
Section: Resultssupporting
confidence: 89%
“…However, there are some reports on preparing CMS-based wood adhesive containing poly(vinyl alcohol) and polyisocyanates [17] or using other carboxymethylated polysaccharide derivative, i.e. carboxymethyl cellulose (CMC) for starch-based wood adhesives [18] or polyisobutylene/CMC pressuresensitive adhesives [19].…”
Section: Introductionmentioning
confidence: 99%
“…UF resin is especially useful for bonding interior wood-based composite boards such as plywood, particleboard, and medium density fiberboard. In recent years, bio-based adhesives prepared from renewable natural resources have been widely researched, such as starch, tannin, and protein (Qiao et al 2014;Zhang et al 2014;Zhang et al 2015). Bio-based adhesives, however, cannot fully replace UF resins in the short period because of their high cost and low production efficiency.…”
Section: Introductionmentioning
confidence: 99%